Mediation as a Medical Dispute Settlement Tool at the Hospital - Situmorang, Benny H.L. (International Journal of Psychosocial Rehabilitation, 2020)
This study aims to determine the mediation efforts in resolving medical disputes in hospitals and to find out the legal protection of doctors in the occurrence of medical disputes in hospitals. This research is empirical normative research. Qualified data as primary data and secondary data. Primary data is obtained from respondents/ sources related to mediation as a medical dispute resolution tool. The secondary data is obtained by collecting various literature. Then the data is analyzed qualitatively. The results of this study indicate that: (1) mediation has the role of preserving living traditions among Indonesian people. Indonesian culture prioritizes deliberation to reach an agreement (consensus) in order to resolve peacefully, even though it must sacrifice personal rights and interests.(2) In any legal relationship between health workers and patients they contain the rights and obligations of each party, the form from law to rights and obligations occur by mediating the events, circumstances or actions of people who are legally connected with the consequences. The rights and obligations of health workers in health law in article 53, namely health workers are entitled to obtain legal protection in carrying out their duties in accordance with their profession and health workers in carrying out their duties are obliged to meet professional standards and respect the rights of patients.